Підсумки інтродукції Dianthus tianschanicus Schischk. на південному сході України - Usmanova, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The results of study of biomorphological peculiarities of Dianthus tianschanicus Schischk. in Donetsk Botanical Gardens of the NAS of Ukraine are gave. It has been stated that while introduced, plants of this species pass the complete cycle of growth and deve lopment, it shows the sufficient rate of species adaptation to the conditions of the region. It has been revealed that the optimal ways of reproduction for D. tianschanicus in culture are semination and grafting. The successfulness of introduction and perspectives for use of this species in landscape gardening in the South-East of Ukraine are estimated.